Prasugrel or clopidogrel in patients with acute coronary syndromes at high thrombotic risk: results from the PROMETHEUS study. (14th October 2021) - Chiarito, M; Cao, D; Zhongjie, Z; Sartori, S; Nicolas, J; Nardin, M; Pivato, C A; Tavenier, A; Rao, S V; Henry, T D; Pocock, S; Dangas, G; et al.
Abstract: Background: Potent P2Y12 inhibitors are recommended on top of aspirin in patients presenting with acute coronary syndrome (ACS). However, guideline recommendations suggest that the optimal antithrombotic strategy should be tailored based on patients thrombotic and hemorrhagic risk profile. Purpose: It is poorly investigated if the benefits derived from potent P2Y12 inhibition in patients with ACS depend on the individual thrombotic risk profile. Our aim was to evaluate if the benefits associated with prasugrel vs. clopidogrel in patients with ACS undergoing percutaneous coronary intervention (PCI) are similar in case of different thrombotic risk profiles. Methods: PROMETHEUS was a multicenter observational study comparing prasugrel vs. clopidogrel in ACS patients undergoing PCI. According to the 2020 ESC guidelines for non-ST elevation-ACS, patients are defined at high thrombotic risk if presenting with a clinical (diabetes mellitus requiring medication, history of recurrent myocardial infarction [MI], multivessel coronary artery disease [CAD], polyvascular [coronary and peripheral] disease, premature (<45 years) CAD, and chronic kidney disease [estimated glomerular filtration rate <60 ml/min/1.73m 2 ]) and procedural (≥3 stents implanted, ≥3 lesions treated, total stent length >60 mm, complex revascularization [left main PCI, bifurcation or chronic total occlusion]) risk features. The primary endpoint was major adverse cardiac events (MACE), a composite of death, MI, stroke or unplanned revascularization. Hazard ratio (HR) and 95% confidence intervals (CI) were calculated using propensity-stratified analysis to assess the effect of prasugrel vs. clopidogrel and with multivariable Cox regression to evaluate the impact of thrombotic risk. Results: Among 16065 patients, 4293 were defined at high thrombotic risk and 11772 at low-to-moderate thrombotic risk. Patients treated with prasugrel had less comorbidities and risk factors than those treated with clopidogrel, both in the high and low-to-moderate thrombotic risk strata. Patients at high thrombotic risk had higher rates of both ischemic and bleeding events at 90 days and at 1 year. Patients treated with prasugrel had a lower adjusted risk of MACE at 1 year (HR 0.86, 95% CI 0.77–0.96), with no significant interaction between effect estimates and thrombotic risk. However, after stratifying the study population by the number of risk factors, there was a significant interaction for a greater reduction in MACE with prasugrel in patients with ≤1 thrombotic risk factor. Conversely, there were no differences in major bleeding among patients treated with prasugrel and clopidogrel. Conclusions: Patients with ACS at high thrombotic risk who undergo PCI are at increased risk of adverse events. Prasugrel, although mainly reserved to patients with lower burden of comorbidities, reduced the risk of ischemic events both in patients at high and low-to-moderate thrombotic risk as compared with clopidogrel. FUNDunding Acknowledgement: Type of funding sources: Private company. Main funding source(s): Daiichi Sankyo and Eli Lilly and Company